Professores reflexivos em processo de mudança na sala de aula de língua estrangeira - Ibarra Papa, Solange Maria de Barros (Cadernos de Linguagem e Sociedade, 2010)
This study aims at investigating the discursive practices of a reflective teacher in the foreign language classroom, as well as to verify whether reflective teaching practice contributes or not to the process of (self)emancipation and social transformation. The main concern is to understand what she says, as well as what she really does in the classroom context. In the analysis I used recordings of interviews and classroom interaction based on SFG and CDA.